Carers’ Attitudes Towards Prescribing of Psychotropic Medications in Children and Adolescents With Intellectual Disabilities in Malta - Noemi Cortis; Sian Edney; Rosemarie Sacco (BJPsych Open)
Aims: This study’s primary aim was to explore carers’ views of psychotropic medication prescribing in children and adolescents with intellectual disability (ID) followed up at Malta’s Intellectual Disability Clinic (IDC). It also aimed to identify carers’ views on nonpharmacological management of challenging behaviour (CB), experiences of Malta’s Child IDC and perceptions of mental illness in children with ID.